Ocena równowagi statycznej z wykorzystaniem platformy posturograficznej u osób słabowidzacych i niewidomych = Evaluation of static balance with the use of the posturographic platform in poorly visionaries and blind persons - Kaźmierczak, Urszula; Kropkowska, Patrycja; Zniszczol, Paweł; Radzimińska, Agnieszka; Strojek, Katarzyna; Goch, Aleksander; Srokowski, Grzegorz; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Kaźmierczak Urszula, Kropkowska Patrycja, Zniszczol Paweł, Radziminska Agnieszka, Strojek Katarzyna, Goch Aleksander, Srokowski Grzegorz, Zukow Walery. Ocena równowagi statycznej z wykorzystaniem platformy posturograficznej u osób słabowidzacych i niewidomych = Evaluation of static balance with the use of the posturographic platform in poorly visionaries and blind persons. Journal of Education, Health and Sport. 2016;6(8):102-112. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59878 http://ojs.ukw.edu.pl/index.php/johs/article/view/3737 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Ocena równowagi statycznej z wykorzystaniem platformy posturograficznej u osób słabowidzacych i niewidomych Evaluation of static balance with the use of the posturographic platform in poorly visionaries and blind persons Urszula Kaźmierczak¹, Patrycja Kropkowska¹, Paweł Zniszczol¹, Agnieszka Radziminska¹, Katarzyna Strojek¹, Aleksander Goch¹, Grzegorz Srokowski², Walery Zukow³ 1. Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii UMK CM w Bydgoszczy 2. Katedra Fizjoterapii, Zakład Fizjoterapii Klinicznej UMK CM w Bydgoszczy 3. WKFZIT, UKW w Bydgoszczy Słowa kluczowe: niewidomi, słabowidzacy, platforma posturograficzna. Key words: blind, partially sighted, platform posturographic. Streszczenie Równowagę można badać na wiele, różnych sposobów. Istnieje wiele testów równoważnych, min. Próba Romberga, test Unterberga, test Babińskiego-Weilla czy próba zbaczania. Inną metodą jest badanie na platformie posturograficznej. Na platformie ocenić możemy równowagę na podstawie przesunięć środka ciężkości ciała. Wychylenia przednio-tylne oraz boczne oceniają stabilność oraz jej zaburzenia. Podczas normalnego, spokojnego stania platforma odbiera położenie środka ciężkości i odnosi jego położenie do czworoboku podparcia w jakim powinien się znajdować. Badania przeprowadzono u 10 osób niewidomych i 13 słabowidzących. Wśród badanych niewidomych było 4 mężczyzn i 6 kobiet. Przedział wiekowy wynosił 43-70 lat ze średnią wieku 61,3.W grupie osób słabowidzących było 5 mężczyzn i 8 kobiet. Badani znajdowali się w przedziale wiekowym 41-69 lat, z czego średnia wieku wynosiła 59,2. Kryterium włączenia były problemy ze wzrokiem. Kryterium wyłączenia stanowiły problemy z równowagą i zawroty głowy. Grupę kontrolną stanowiło 25 osób bez problemów wzrokowych, o średniej wieku 63,9 lat. Osoby badane to uczestnicy turnusów rehabilitacyjnych dla niewidomych i słabowidzących odbywających się w Ośrodku Intercor przy ulicy Powstańców Wielkopolskich 33 w Bydgoszczy. Osoby niewidzące charakteryzują się gorszą równowagą niż osoby widzące prawidłowo. Osoby słabowidzące utrzymują równowagę na zbliżonym poziomie do osób całkowicie widzących. Abstract Stability can be examined for many different ways. There are a number of stability tests – Attempt Romberg, test Unterberg, Babinski-Weill test Oran attempt to drift. Another method test the platform posturographic. On the platform, we can evaluate the balance on the basis of shifts the center of gravity of the body. Swing of the anteroposterior and lateral valuate stability and its disorders. During normal quiet standing platform receives the position of center of gravity of the quadrangle refers to its position and support what is should be. The study included 10 people who are blind and visually impaired 13. Among the respondents, the blind were 4 men and 6 women. The age range was 43-70 years old with an average age of 61.3. In the group of visually impaired were 5 men and 8 women. The subjects were aged 41-69 years, with an average age of 59.2. The inclusion criteria were vision problems. Exclusion criteria were problems with balance and dizziness. The control group consisted of 25 people with sight problems, with an average age of 63.9 years. The subjects that participants rehabilitation camps for the blind and visually impaired held at the Centre Intercor Street Powstańców Wielkopolskich 33 in Bydgoszcz. Blind people have a worse balance than the sighted correctly. Visually impaired people maintain the imbalance on a similar level to fully sighted people.